2015
DOI: 10.1055/s-0040-1709755
|View full text |Cite
|
Sign up to set email alerts
|

Management of Soft Tissue Injuries – Case Series

Abstract: Soft tissue injuries, whether isolated or in combination with other injuries, are amongst the most common traumatic craniofacial injuries encountered in our day to day practice.Soft tissue injuries may involve the skin, subcutaneous tissue, underlying muscle or a combination of any of these elements. Although rarely life-threatening, the treatment of these injuries can be complex and may have significant impact on the patients' facial aesthetics and function. Hence one should know the “do's and don'ts”.Disfigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Soft-tissue facial injuries are common in children involved in maxillofacial trauma due to the greater cranial mass-to-body ratio and also quite frequent than fractures in children who have encountered facial trauma, specifically in younger children whose bones have the distinct ability to resist fracture [5]. The force of impact and the injury type is directly related to the severity of the injury sustained [5].…”
Section: Introductionmentioning
confidence: 99%
“…Soft-tissue facial injuries are common in children involved in maxillofacial trauma due to the greater cranial mass-to-body ratio and also quite frequent than fractures in children who have encountered facial trauma, specifically in younger children whose bones have the distinct ability to resist fracture [5]. The force of impact and the injury type is directly related to the severity of the injury sustained [5].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies in India have reported that ∼72% of the trauma cases resulted in huge soft tissue loss [ 1 , 2 ]. Soft tissue damage also occurs due to ageing, disease, tumours, congenital defects and acquired deformities [ 3 ].…”
Section: Introductionmentioning
confidence: 99%